Law Enforcement Activities in Peacekeeping and Multinational Military Operations: The Cases of Haiti and Afghanistan (2019)
The chapter is devoted to the legal difficulties military missions face when fighting crime in times of armed conflict. Organized crime is a destabilizing factor that often interlinks with and is particularly prevalent in situations of armed conflict. Multinational military operations are therefore frequently simultaneously engaged in genuine military operations as well as traditional law enforcement and policing tasks and thereby operate at the intersection of the laws of armed conflict and IHRL. The question which law governs law enforcement operations such as counter-drug operations in the context of an armed conflict, that is, in a scenario in which the laws of armed conflict undoubtedly apply, remains contested. What lessons can be learned and how has this problem been dealt with in practice? Can these lessons be transposed to contemporary multinational military operations?